Cash Management and Bank’s Financial Performance: Evidence from selected Deposit Money Banks in Nigeria - Ali, Peter; Njoku, Peter N. O.; Ugoani, John N. N.; Nwaorgu, O. C.; Ukeje, Okanta S (AFRE (Accounting and Financial Review), 2021)
This study empirically examined the effects and implications of cash management of DMBs in Nigeria. The variables studied were Cash to total asset, Operating cash to total asset, Investing cash to total asset, Financing cash to total asset, Bank size, Bank age, proxied for cash management and Return on Asset used to represent financial performance. Data used for this study were from secondary sources and were generated from the annual reports and accounts of the selected DMBs for the period 2014–2018. The results show that while operating cash to total asset of bank, investing cash to total asset and bank size have no significant effect on financial performance of DMBs, financing cash to total asset and bank age have a significant and positive effect on financial performance of deposit money bank (DMBs). However, cash to total asset has a significant negative effect on financial perfor-mance of banks. The study concludes that cash positions, which can lead to liquidity risk has to be managed because it has tendency to compound other risks. It further highlighted that adequate attention should be paid on the use and reserves of cash among banks in Nigeria. This study recommends that banks should adopt optimum cash management model for efficiency and effectiveness. Stringent regulatory policies in this regard must be reviewed in such a way that they can be relaxed, to encourage effective liquidity manage-ment measures.